Field validation of POCIS for monitoring at underwater munitions sites. (25th June 2018) - Rosen, Gunther; Lotufo, Guilherme R.; George, Robert D.; Wild, Bill; Rabalais, Lauren K.; Morrison, Shane; Belden, Jason B.
Abstract: The present study evaluated polar organic chemical integrative samplers (POCIS) for quantification of conventional munitions constituents, including trinitrotoluene (TNT), aminodinitrotoluenes, diaminonitrotoluenes, dinitrotoluene, and hexahydro‐1, 3, 5‐trinitro‐1, 3, 5‐triazine (RDX) in a field setting. The POCIS were deployed at varying distances from the commonly used explosive formulation composition B (39.5% TNT, 59.5% RDX, 1% wax) in an embayment of Santa Rosa Sound (Pensacola, FL, USA). Time‐weighted averaged water concentrations from a 13‐d deployment ranged from 9 to 103 ng/L for TNT and RDX, respectively, approximately 0.3 to 2 m from the source. Concentrations decreased with increasing distance from the source to below quantitation limits (5–7 ng/L) at stations greater than 2 m away. Moderate biofouling of POCIS membranes after 13 d led to a subsequent effort to quantify potential effects of biofouling on the sampling rate for munitions constituents. After biofouling was allowed to occur for periods of 0, 7, 14, or 28 d at the field site, POCIS were transferred to aquaria spiked with munitions constituents. No significant differences in uptake of TNT or RDX were observed across a gradient of biofouling presence, although the mass of fouling organisms on the membranes was statistically greater for the 28‐d field exposure. The present study verified the high sensitivity and integrative nature of POCIS for relevant munitions constituents potentially present in aquatic environments, indicating that application at underwater military munitions sites may be useful for ecological risk assessment. Environ Toxicol Chem 2018;37:2257–2267. Published 2018 Wiley Periodicals Inc. on behalf of SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.